Low Birth Weight, β-Cell Function and Insulin Resistance in Adults: The Brazilian Longitudinal Study of Adult Health - Branda, Julia Ines F.; de Almeida-Pititto, Bianca; Bensenor, Isabela; Lotufo, Paulo A.; Ferreira, Sandra Roberta G. (Frontiers in Endocrinology, 2022)
Background: Adverse intrauterine environment – reflected by low birth weight (LBW) – has been linked to insulin resistance and type 2 diabetes later in life. Whether β cell function reduction and insulin resistance could be detected even in middle-aged adults without overt diabetes is less investigated. We examined the association of LBW with β cell function and insulin sensitivity in non-diabetic middle-aged adults from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Methods: This is a cross-sectional analysis of 2634 ELSA-Brasil participants aged between 34 and 59 years, without diabetes. Participants were stratified according to LBW defined as <2.5 kg and their clinical data were compared. HOMA-IR, HOMA-β, HOMA-adiponectin, TyG index, QUICKI and TG/HDL were calculated and their association with LBW were tested using multiple linear regression including adjustments suggested by Directed Acyclic Graphs and propensity score matching was applied. Results: The sample (47.46.3 years) was composed of 57.5% of women and 9% had LBW. Subjects with LBW and normal-weight reported similar BMI values at the age of 20 years and current BMI was slightly lower in the LBW group. In average, cardiometabolic risk profile as well as indexes of β cell function and insulin sensitivity were within normal ranges. In regression analysis, log-transformed HOMA-β – but not with the other indexes – was associated with LBW (p=0.014) independent of sex, skin color, prematurity and family history of diabetes. After applying propensity-score matching in a well-balanced sample, HOMA-AD and TG/HDL indexes were associated with LBW. Conclusion: The association between LBW and insulin sensitivity markers may occur in healthy middle-aged adults before overt glucose metabolism disturbances. Our data are coherent with the detection of early life events consequent with insulin resistance markers that could contribute to the risk of glucose metabolism disturbances.